Identification of Leading Plantation Commodities and Financial Feasibility of Farming in Kaur Regency - Jupi Piji Aksen; Widiatmaka Widiatmaka; Setyardi Pratikamulya (Politeknik Siber Cerdika Internasional, 2026)
Background: The plantation sector has a strategic role in driving regional economic growth and improving community welfare, particularly in areas whose economic structure is dominated by agriculture. Kaur Regency is one of the regions where the agricultural and plantation sectors contribute significantly to the Regional Gross Domestic Product (GRDP). However, the development of plantation farming still faces obstacles such as production costs, price fluctuations, and capital limitations. Objective: This study aims to identify leading plantation commodities and analyze their financial feasibility. Methods: The determination of leading commodities was carried out using the Location Quotient (LQ) and Shift Share Analysis (SSA) methods based on secondary data (BPS Kaur Regency 2019 and 2024) and primary field survey data. Financial feasibility analysis used indicators including Net Present Value (NPV), Benefit–Cost Ratio (B/C), and Internal Rate of Return (IRR). A total of 45 farmers were selected as respondents through purposive sampling: 18 oil palm farmers, 15 coconut farmers, and 12 rubber farmers from three leading commodity sub-districts in Kaur Regency. Results: The analysis results show that oil palm, coconut, and rubber are leading commodities with comparative and competitive advantages in Kaur Regency. Financially, oil palm recorded the highest NPV (IDR 361,514,078; B/C ratio 9.21; IRR 59.9%), followed by coconut (NPV IDR 260,159,827; B/C ratio 5.52; IRR 34.57%), and rubber (NPV IDR 111,185,336; B/C ratio 4.21; IRR 44.73%). All three commodities remain feasible under sensitivity scenarios of a 10% cost increase and a 10% revenue decrease. Conclusion: Thus, the development of these three commodities has the potential to increase farmers' income and strengthen the regional economy.